The vegan athlete's cookbook : protein-rich recipes to train, recover and perform - Bean, Anita (Bloomsbury Sport, 2021)
Exciting, healthy and tasty vegan recipes with the nutrients you need to train, recover and perform. Whether you already live a vegan lifestyle, embrace a meat-free day each week or you simply want to try some amazing flavour combinations, The Vegan Athlete's Cookbook will help you create easy, nutrient-packed meals to support your training goals. With a focus on performance, every recipe has been created to provide a high level of nutrients that will fuel your body. All the main meal recipes supply at least 20 g of protein per serving, the optimal amount needed for muscle recovery. As well as delicious everyday recipes and cooking tips, the book also contains evidence-based advice on how to fuel your workouts and maximise your performance. It debunks vegan myths, demystifies sports nutrition and will help you gain the confidence to create delicious, nourishing meals that will boost your fitness.